From mental disorders to social suffering: Making sense of depression for critical theories. (November 2019) - Sik, Domonkos
This article aims at grounding critical theories with the help of psy discourses. Even if the relationship between the two disciplines has always been a controversial one, the article argues that therapeutic knowledge that accesses empirical forms of social suffering may offer important insights for critical theory. This general argument is demonstrated by complementing the theories of Bourdieu and Habermas with a clinical description of depression. First, the limitations of the capabilities of these influential theories in terms of how they can be used to conceptualize the variety of social suffering are introduced. Second, the psy discourses on depression are reviewed to identify and highlight latent references to the social. Third, by combining models of depressive suffering and various distortions of integration, an extended normative basis is elaborated. Instead of solely criticizing inequalities or distortions of communication, those social constellations are criticized that trap actors by producing a homogenous pattern of suffering.